Pentoxifylline and enalapril and its effects on polycythemia induced by hypobaric hypoxia in mice - Gamboa, J.; Rivera-Ch, M; León-Velarde, F.; Salazar , M.; Monge-C., C. (Acta Andina, 2025)
To assess the prophylactic and therapeutic effects of enalapril and pentoxifylline on hypoxia-induced polycythemia in laboratory mice, 70 Swiss male mice of 3 to 4 months of age were studied. They werw divided in 2 groups: pentocifylline group (n=39) anda enalapril group (n=31). Each group was further divided in a prophylactic group which received the drug before exposure to intermittent hypobaric hypoxia (IHH) and a therapeutic group which received the drug after exposure to IHH. Each subgroup had their respective control. Exposure to IHH was performed through a hypobaric chamber which simulated an altitude equivalent to 4 500 m above sea level, 22 hours a day. Weight and hematocrit were measured weekly. Time-course of body weight did not show substantial differences between treated and control animals in prophylactic and therapeutic groups in both pentoxifylline and enalapril groups. There was a significant hematocrit decrease 36 and 47 days after the beginning of prophylaxis in pentoxifylline group. In enalapril prophylactic group hematocrits were significantly lower in treated animals. We conclude that both drugs are effective when they are used prophylactically before exposure to IHH. It is suggested that the drugs might exert their effects through a partial blockade of erythropoietin (EPO) production.